Identificação da paleovegetação associada as áreas de cerrado na mesorregião centro oriental paranaense - Villwock, Fernando Henrique (2018)
Brazil has continental dimensions, and its territory presents great contrast in the phytogeographic point of view. Among the vegetation found is the Cerrado, which in the past occupied 22% of the territory, mainly covering the Brazilian central portion, however half was transformed due to anthropic actions. In the state of Paraná, the Cerrado had an approximate area of 1,700 km2, nevertheless, today only islands of this vegetation are observed. In this perspective the research has as study area the municipality of Jaguariaíva, in the Mid-East Region of Paraná. In the municipality is located the largest preservation area of the Cerrado in Paraná, the State Park of the Cerrado, with 420 hectares, in addition to presenting fragments scattered throughout its territory. The research aimed to verify the paleovegetation associated with Cerrado areas, justifying the need for studies related to the Cerrado development factors in Paraná. Two field trials were carried out in the years 2016 and 2017, with soil samples collected through a test tube and botanical material collection. In addition to the samples, samples obtained from two blocks at the Abrigo Jaguariaíva 1 Archaeological Site, with a depth of 127 cm in the first and 65 cm in the second, were collected by the team from the Museu Paranaense through systematic archaeological excavations with sieving. From the botanical collection and the analysis of the vegetation, it was possible to infer through the production of canopies, that the physiognomy of the local Cerrado varies from Cerrado Typical to Cerrado Ralo, the families present in the slope were still inferred, being: Asteraceae, Celastraceae , Erythroxylaceae, Fabaceae, Myrtaceae, Mimosaceae, Poaceae and Myrtaceae. In the laboratory the description, the granulometry and the processing of the soil samples were carried out. The protocol was given via acid burning (hydrochloric acid), aiming the extraction of phytoliths, after which the slides were observed under a microscope. Having the phytolytic assemblies for a given "proxy", indications referring to the paleoenvironments correlated to the studied area were made. In the samples from the Archaeological Site, the phytolith associated with the family Cucurbitaceae was found, dating to over 2,868 - 3,073 years AP, corroborating the practice of agriculture, as well as indicating the indigenous diet. The analysis of the morphotypes present in the soil profiles indicate the concentration of the Bilobate morphotype (family Poaceae), subject to water stress (morphotype Bulliform). From the above it is considered that the presence of rural vegetation is old, surpassing 7680-7516 AP years